’Scientific’ Versus ’Traditional’ Cultures: Understanding cultural contents for health ’Development’ in Nepal - Thapa, Janardan (Himalayan Journal of Sociology and Anthropology, 2009)
No Abstract available Himalayan Journal of Sociology & Anthropology Vol.2 2005 p.18-47